Design and hardware-in-the-loop evaluation of a time dissemination framework for drone operations in urban environments - Negru, Sorin Andrei; Petrunin, Ivan; Guo, Weisi; Tsourdos, Antonios (Institute of Electrical and Electronics Engineers (IEEE), 2023)
With the advent of UAVs (Unmanned Aerial Vehicles) several companies started to offer services, in urban, semi-urban, and rural regions. Although GNSS (Global Navigation Satellite System) can disseminate time information to different platforms, external factors may degrade the signal quality and lead to erroneous time synchronization. The paper is presenting a resilient time dissemination framework, using a wireless 802.11ax protocol and NTP (Network Time Protocol) for the synchronization aspect. A time server, formed by a rubidium clock, a GNSS receiver, and time information provided by NPL (UK’s National Physical Laboratory) traceable to UTC, dictates the time to all the users within the WLAN (Wireless Local Area Network). To evaluate the proposed framework, a lab-based HIL (Hardware in the Loop) simulation is performed using two Jetson Nanos as CC (Companion Computer) and a Pixhawk 2.4 as FCU (Flight Control Unit) representing the end-users in the dissemination framework. In this way, all the communication links are tested and evaluated. Results showed that the two platforms can be synchronized to the time server as an alternative time source, achieving an average RTT (Round Trip Delay) of 8 ms from the Research and Innovation timing node to the FCU, and an average time offset of -0.2 ms.
Keywords: GNSS; time dissemination; oscillators; drift; urban mobility; UAVs; synchronization